Persistence of the immune response at 5 years of age following infant immunisation with investigational quadrivalent menACWY conjugate vaccine formulations. (24th May 2012) - Khatami, A; Snape, MD; Davis, E; Layton, H; John, T; Yu, L-M; Dull, PM; Gill, CG; Odrjlin, T; Dobson, S; Halperin, SA; Langley, JM; et al.
Abstract : Introduction: Meningococcal serogroup C (MenC) conjugate vaccines are used routinely for infant immunisation in Canada and Europe. Quadrivalent serogroup A, C, W−135 and Y meningococcal (MenACWY) conjugate vaccines are licensed in Europe and North America, and recommended for routine immunisation of adolescents in the United States. Methods: In an open-label, randomised controlled trial in the UK and Canada, we evaluated the persistence of immune response at 40 and 60 months of age after different schedules of two MenACWY-CRM conjugate vaccine formulations administered in infancy with MenC conjugate and MenACWY polysaccharide vaccines at 12 months of age. Two control groups were also recruited at 60 months, who had been immunised as infants or toddlers with MenC vaccines according to country-specific schedules. Results: 382 children enrolled in 12 groups (22 to 40 per group) were followed up. By age 60 months, 3-11% of children primed and boosted with MenACWY-CRM had serum bactericidal antibody (using human complement [hSBA]) titres ≥1:8 against serogroup A meningococci, 14-45% against serogroup C, 57-84% against serogroup W-135 and 42-69% against serogroup Y. These proportions were similar for children primed with MenC and boosted with MenACWY-CRM except for serogroup C (59%). In age-matched control children at 60 months of age, percentages with hSBA titres ≥1:8 were 0-3%, 29-53%, 33-36% and 10-29% against serogroups A, C, W-135 and Y, respectively. Conclusions: Immune responses against all serogroups wane following infant immunisation with MenACWY-CRM vaccines, most markedly against serogroup A. Better persistence of serogroup C hSBA titres was observed in schedules with MenC conjugate vaccine priming doses, however use of a booster MenACWY conjugate vaccine could provide broader protection against meningococcal disease.